Thermally stimulated conductivity in InGaAs/GaAs quantum wire heterostructures - Iliash, S.A.; Kondratenko, S.V.; Yakovliev, A.S.; Kunets, Vas.P.; Mazur, Yu.I.; Salamo, G.J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Thermally stimulated conductivity of the InGaAs-GaAs heterostructures with quantum wires was studied using different quantum energies of exciting illumination. The structures reveal long-term photoconductivity decay within the temperature range 100 to 200 K, and effect of residual conductivity after turning-off the illumination. Analyzing the data of thermally stimulated conductivity, the following energies of electron traps were found: 90, 140, and 317 meV. The role of deep traps in recombination process as well as the photoconductivity mechanism was discussed.